Endocrine immune-related adverse events: Adrenal, parathyroid, diabetes insipidus, and lipoatrophy. Issue 3 (May 2022) - Atkinson, M.; Lansdown, A.J.
Abstract : Immune checkpoint inhibitors are being prescribed increasingly widely for a range of malignancies. They are effective at treating certain cancers, but also have significant side effects. Evidence suggests that efficacy is greatest in patients who experience one or more immune-related adverse events (irAEs). Common irAEs include skin and hepatic reactions, and a range of immune-related endocrinopathies. These include hypophysitis, thyroid disease, and autoimmune diabetes mellitus, and rarer endocrinopathies such as primary adrenal insufficiency, diabetes insipidus, parathyroid disease, autoimmune polyglandular syndrome, lipodystrophy, and ACTH-dependent Cushing's syndrome. Herein, we review the current literature related to these rarer immunotherapy-induced endocrinopathies.